2007
DOI: 10.1353/dem.2007.0031
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use patterns across teens’ sexual relationships: The role of relationships, partners, and sexual histories

Abstract: By using data from the National Longitudinal Study of Adolescent Health, we examine how adolescent relationship characteristics, partner attributes, and sexual relationship histories are associated with contraceptive use and consistency, incorporating random effects to control for respondent-level unobserved heterogeneity. Analyses show that teens' contraceptive use patterns vary across relationships. Teens with more-homogamous partners, with more-intimate relationships, and who communicate about contraception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
131
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(142 citation statements)
references
References 56 publications
9
131
1
1
Order By: Relevance
“…The reason for this unexpected finding is not apparent and was not explained by additional statistical tests. * However, a possible reason for the difference between the findings of this study and those of other studies [1][2][3][4][7][8][9][10][11][12][13][14][15][16][17] could be that negative reproductive health outcomes are more common in nonmarital relationships and among adolescents than within marriage and among older women, respectively. Moreover, women are often able to use contraceptives covertly, and exercise some degree of *A number of models were created to explore the findings, including ones that examined possible interactions between age differences and other variables (particularly region) or that treated age difference as a continuous variable.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The reason for this unexpected finding is not apparent and was not explained by additional statistical tests. * However, a possible reason for the difference between the findings of this study and those of other studies [1][2][3][4][7][8][9][10][11][12][13][14][15][16][17] could be that negative reproductive health outcomes are more common in nonmarital relationships and among adolescents than within marriage and among older women, respectively. Moreover, women are often able to use contraceptives covertly, and exercise some degree of *A number of models were created to explore the findings, including ones that examined possible interactions between age differences and other variables (particularly region) or that treated age difference as a continuous variable.…”
Section: Discussioncontrasting
confidence: 98%
“…[1][2][3][6][7][8] The studies that have examined associations between partners' age differences and contraceptive behavior have concentrated on adolescent females' nonmarital relationships and on whether protection was used against STIs (especially HIV). [1][2][3][4][7][8][9][10][11][12][13][14][15][16][17] The emphasis on adolescents and on nonmarital relationships may divert attention from more common age asymmetries and from the risks that may exist in such relationships. For instance, age differences in marital relationships are usually of little public interest, unlike situations involving unmarried adolescents.…”
mentioning
confidence: 99%
“…The single study that linked contraceptive use and relationship quality found that use was correlated with both marital and sexual satisfaction. 17 In developed countries, researchers have primarily examined relationship quality and contraceptive use among unmarried adolescents, 21,22 and often focus on condom use. 20,23 Few studies have focused on this topic among adults in steady or long-term relationships, and several include only young adults in their sample.…”
mentioning
confidence: 99%
“…Parents and health and education professionals tend to be wary of romantic relationships between teens because such relationships can lead to sexual intimacy. But it may be more important to identify the critical characteristics of teenagers' romantic relationships: Adolescent sexual activities are more likely to be safe, wanted, and gratifying when relationships are equaldthat is, not characterized by large age differences between girls and older boyfriendsdand when teenagers feel satisfied, experience intimacy, and are able to discuss contraception openly within their relationships (Houts, 2005;Manlove, Ryan, & Franzetta, 2007;Stone & Ingham, 2002;Widman, Welsh, McNulty, & Little, 2006). Third, adolescent sexual health requires connectedness with parents and other caregivers (C).…”
mentioning
confidence: 99%